(untitled) (Revista Ciência Agronômica, 2020)
Large-scale commercial production of pitaya is recent and there is little information on pollination and fruiting in this crop. Therefore, the objective of the present study was to investigate if the Africanized honeybee (Apis mellifera), frequent visitor of pitaya flowers (Hylocereus undatus and H. polyrhizus), plays any relevant role in the pollination of these cacti species, both in terms of fruit quantity and fruit quality. The study consisted of four treatments: natural pollination; restricted pollination; nocturnal pollination and pollination by A. mellifera, and all fruits were harvested and analyzed at 30 days after setting. Each treatment was evaluated in the number of fruits produced, total weight of the fruit; skin weight; pulp weight; longitudinal and transverse size; number of seeds; pH; acidity; total soluble solids (TSS); and TSS/total acidity ratio. Results showed that these pitaya species differ in their dependence on biotic pollination for the production, weight and quality of fruits. H. undatus did not depend on bees to set fruits but needed the moth Agrius cingulata to improve yield quality with larger and heavier fruits. On the other hand, H. polyrhizus depended on biotic pollination to maximize fruit production and Apis mellifera specifically to increase size and weight of fruits. In addition, the tested types of pollination influenced little the physical-chemical characteristics of fruits, being only relevant in the reduction of the pH in flowers pollinated by A. mellifera.